Variations of Language Slang on Instagram Social Media - Irma Nuraeni Salsabila; Vika Fransisca; Nur Alifah (Syntax Corporation, 2022)
Through the large number of Instagram users in Indonesia, slang can be easily found in photo or video descriptions and comments made by uploading. Instagram is a program for sharing photos and videos that allows users to take photos or videos, implement digital effects for photos or videos, and upload them to other social media services, to Instagram. This study aims to determine the variation of slang on social media Instagram. This research method is included in the category of qualitative descriptive research, which then provides a description or explanation clearly regarding the form, meaning, category and role of slang in social media Instagram. The data sources used in this study are photos or videos uploaded by Instagram social media users to an account. The results showed that in Instagram there are several forms of sland including: 1) abbreviated form, 2) shortened form, 3) funny pronunciation errors, 4) home form, 5) community form. So it can be concluded that the research found 5 forms of slang on Instagram social media.